2022
DOI: 10.3389/fendo.2022.997631
|View full text |Cite
|
Sign up to set email alerts
|

Free, bioavailable 25-hydroxyvitamin D levels and their association with diabetic ketoacidosis in children with type 1 diabetes at diagnosis

Abstract: BackgroundConsidering the roles of 25-hydroxyvitamin D (25OHD) in glucose homeostasis and immune modulation, vitamin D deficiency may be related to the development of type 1 diabetes (T1DM) and diabetic ketoacidosis (DKA). We evaluated the total, free, bioavailable 25OHD levels and vitamin D binding protein (VDBP) levels and genotypes between T1DM patients and controls.MethodsThis retrospective, cross-sectional study included 84 children with T1DM (38 boys and 46 girls, 8.0 ± 3.6 years) and 1:1 age- and sex-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Similar to our findings, in a study of children with type 1 diabetes mellitus, the mean BAVD levels in the control group were found to be between the two study groups (DM with or without ketoacidosis). Although there was no significant difference between the study and control groups, BAVD levels were significantly reduced in type 1 diabetes mellitus with ketoacidosis 27 …”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Similar to our findings, in a study of children with type 1 diabetes mellitus, the mean BAVD levels in the control group were found to be between the two study groups (DM with or without ketoacidosis). Although there was no significant difference between the study and control groups, BAVD levels were significantly reduced in type 1 diabetes mellitus with ketoacidosis 27 …”
Section: Discussionmentioning
confidence: 62%
“…Although there was no significant difference between the study and control groups, BAVD levels were significantly reduced in type 1 diabetes mellitus with ketoacidosis. 27 Previous studies have reported that the positive effects of vitamin D on the innate and adaptive immune system and immune response modulation may prevent lung and cardiovascular system damage and decrease thrombotic events. 28 Furthermore, vitamin D may prevent virus entry and replication by protecting the integrity of physical barriers and may reduce organ damage and thrombotic events by increasing levels of angiotensin-converting enzyme 2, nitric oxide, and antioxidants or by reducing inflammatory cytokine and free radical levels.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies that evaluate the effect of acidosis on 25OHVitamin D levels, in general, report lower levels in patients presenting with acidosis. Choe et al recently reported lower levels of 25OHVitamin D in children with T1D compared to controls (16 vs. 19.9 ng/mL; p < 0.001) [11]. In agreement with our results, they did not find any differences between the T1D group presenting without acidosis and the control group (17.6 vs. 19.9 ng/mL), whereas the difference remained in the T1D group with acidosis compared with controls (15 vs. 19.9 ng/mL; p < 0.001).…”
Section: Effect Of Acidosis On 25ohvitamin Dmentioning
confidence: 92%
“…A clear explanation of the pathophysiological pathways leading to the reported difference in 25OHVitamin D levels in patients with DKA at the moment of T1D onset is still lacking. Choe et al explored in some depth the levels of total, free, and bioavailable 25OHVitamin D, as well as vitamin D binding protein (VDBP) [11]. They concluded that T1D patients presented significantly lower total but higher free 25OHVitamin D levels than healthy children.…”
Section: Effect Of Acidosis On 25ohvitamin Dmentioning
confidence: 99%
See 1 more Smart Citation